The Relationship Between Juvenile Delinquency and the Low Learning Achievement of the Nurul Qodiri Islamic Boarding School Students - Andika Ari Saputra; Rizky Hidayatullah; Yansen Alberth Reba; Yoppry Tanjung; Nova Lina Eldasari; Lailatul Inayah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2021)
This study aims to determine: the relationship between juvenile delinquency and the low learning achievement of the students of the Nurul Qodiri Islamic Boarding School. This research is a correlation research. The variables studied were juvenile delinquency and low learning achievement. The data collection method uses a scale, the tool is in the form of a juvenile delinquency scale and a scale of low learning achievement. The validity test was carried out with the help of a computer program SPSS 22 for windows. Reliability test usingtechnique Cronbach's alpha, obtained p = 0,540 for juvenile delinquency variable and p = 0,544 for low learning achievement variable. The analysis technique used is descriptive and inferential statistics with SPSS 22 for windows program. The results showed that there was a relationship between juvenile delinquency and the low learning achievement of the students of the Nurul Qodiri Islamic Boarding School of 0.335, the probability number of Ts 5% was 0.000 (p <0.05).(p<0,05).